PENGARUH PELATIHAN LARI TIGA SUDUT DAN SIDE JUMP SPRINT TERHADAP DENYUT NADI ISTIRAHAT - Budiarsa, Gede (Universitas Pendidikan Ganesha, 2013)
This study aimed to determine the effect of the training run three corners (corner three drill) and jump side sprint to the decline in resting pulse rate class VII student son SMP N 2 Singaraja. Data resting pulse rate measured by the radial pulse rate test (palpation). Data were analyzed by independent t-test at significance level (Î±) of 0.05, using the SPSS 16.0 program. Results of data analysis showed a decrease in the average value of the variable pulse break. In the training group ran three corners a decline of 21.55 beats per minute, side jump sprint training group a decrease of 18.35 beats per minute and the control group decreased by 8 beats per minute. For one-way anava test results data is resting pulse rate per minute to get the significance F value (0,000) is smaller than the value of Î± (Sig <0.05) this shows the difference between the effect of the training run three corners and jump side sprint to the resting pulse rate. LSD test results data is resting pulse rate per minute to get the smallest value is 3.200 * for group training run three corners, 10,600 * for the side jump sprint training group and 13,800 * for the control group. From the results obtained LSD training run three angles have the smallest value compared side jump sprint training group or a control group. For data resting pulse rate, training is the best training effect with the smallest LSD results. This is because the smaller the frequency of a person's resting pulse rate, the better the physical condition owned.